TRANSACTIONS BETWEEN AFFILIATES. - Paton, W. A. (The Accounting Review, 1945)
Abstract It is generally agreed nowadays- among both teachers of accounting and professional accountants-that "accounting is based on cost." The significance of this proposition, however, has not been adequately clarified. It certainly does not mean that accounts and financial statements continuously show the total acquisition costs of the various factors listed in such statements; absorption of costs through depreciation, depletion and amortization is a major feature of the normal process of accounting. It does not mean that shrinkage in value of inventory items must be ignored; recognized inventory methods provide for appropriate write-down in the case of damaged or obsolete elements and for absorption of costs considered to be nonrecoverable and hence not assignable to future revenues-as a result of changes in prices. It does not preclude partial or complete write-off of assets such as investments when there is convincing evidence of permanent impairment, or total disappearance, of value (although not all accountants would take the position that partial write-off prior to disposition is required). It does not overlook the fact that conventional cost procedures result in cost compilations that are nothing better than reasonable estimates of allocated costs incurred to date, especially in the case of work in process and finished goods.